Romanian rural tourism development through European financial support measures - Elena Sima (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
Encouraging the development of tourism activities represents an occupational alternative for the rural labour force. It is a significant way to diversify the economic activities in the countryside. Finally, it is a stabilizing factor for the rural population. The objective of this paper is to investigate the Romanian effort to develop and promote tourism in the rural area with support from the European funds. Statistical data was completed from articles and studies published in specialty journals, as well as in government documents. The results allow us to conclude that the natural resources and landscape, the social capital, the rural governance, the business and social networks as well as the information and communication technologies have dynamic and complex influences upon the entrepreneurial activity in the rural areas.
Keywords: Q14; L83; R58; 330; rural tourism; European funds; investments; Romania